2021
DOI: 10.3390/ijerph18105382
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Childbirth and Preferences for Prevention Services among Urban Pregnant Women in a Developing Country: A Multicenter, Cross-Sectional Study

Abstract: This study aimed to examine fear of childbirth and willingness to pay for fear-prevention services in pregnant women. A multicenter, cross-sectional study was conducted on pregnant women in two obstetric hospitals in Vietnam. The Fear of Birth Scale was utilized to evaluate fear of childbirth. Multivariable, generalized linear regression and logistic regression models were performed to identify associated factors with fear of childbirth, demand, and willingness to pay for prevention services. Of 900 pregnant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
(55 reference statements)
1
6
0
Order By: Relevance
“…The description of the study design had been published elsewhere ( Nguyen et al., 2021 ). In brief, we included pregnant women who were aged 18 years or above, agreed to participate in the study by giving written informed consent and had no physical and mental impairment that affected the ability to answer the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…The description of the study design had been published elsewhere ( Nguyen et al., 2021 ). In brief, we included pregnant women who were aged 18 years or above, agreed to participate in the study by giving written informed consent and had no physical and mental impairment that affected the ability to answer the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…The severity of FOC in women varies from mild to severe (7)(8)(9)(10). Severe FOC is a pathological disorder that has negative consequences on mental health (depression, anxiety, and post-traumatic stress disorder) (1,9), family relationships (increased marital conflict, and adverse emotional and behavioral consequences on the relationship between mother and child) (2,8,11,12), and pregnancy (avoiding pregnancy, abortion, less pain tolerance, increased use of anesthetics during labor, prolonged labor, cesarean section) (1,9,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, fear of childbirth (FOC) affects about 7.6–8.8% of pregnancies [ 2 , 3 ] and is more prevalent and more severe in primiparous women compared with multiparous women [ 4 , 5 ]. Of course, in some studies, the fear of childbirth has been reported to be higher in multiparous women [ 6 , 7 ]. Parity can affects the content of this fear.…”
Section: Introductionmentioning
confidence: 99%
“…prevalent and more severe in primiparous women compared with multiparous women [4,5]. Of course, in some studies, the fear of childbirth has been reported to be higher in multiparous women [6,7]. Parity can affects the content of this fear.…”
mentioning
confidence: 99%